Normal ganglionic transmission in the presence of acetylcholine block by sea snake (Enhydrina Schistosa) venom - Chan, K.E.; Chang, P. (Elsevier, 1971)
Enhydrina schistosa venom abolished the contraction of the nicitating membrane of the cat produced by intra-arterial injection of acetylcholine into the superior cervical ganglion. During the block, there was no apparent failure of ganglionic transmission. The significance of these findings is discussed in relation to the role of acetylcholine as a neurotransmitter in sympathetic ganglia. © 1971.